Interaction of high molecular weight kininogen binding proteins on endothelial cells - Joseph, Kusumam; Tholanikunnel, Baby G.; Ghebrehiwet, Berhane; Kaplan, Allen P. (Thrombosis and Haemostasis, 2004)
Cell surface proteins reported to participate in the binding and activation of the plasma kinin-forming cascade includes gC1qR, cytokeratin 1 and u-PAR. Each of these proteins binds high molecular weight kininogen (HK) as well as Factor XII. The studies on the interaction of these proteins, using dot-blot analysis, revealed that cytokeratin 1 binds to both gC1qR and u-PAR while gC1qR and u-PAR do not bind to each other. The binding properties of these proteins were further analyzed by gel filtration. When biotinylated cytokeratin 1 was incubated with either gC1qR or u-PAR and gel filtered, a new, higher molecular weight peak containing biotin was observed indicating complex formation. The protein shift was also similar to the biotin shift. Further, immunoprecipitation of solubilized endothelial cell plasma membrane proteins with anti-gC1qR recovered both gC1qR and cytokeratin 1, but not u-PAR. Immunoprecipitation with anti-u-PAR recovered only u-PAR and cytokeratin 1. By competitive ELISA, gC1qR inhibits u-PAR from binding to cytokeratin 1; u-PAR inhibits gC1qR binding to a lesser extent and requires a 10-fold molar excess. Our data suggest that formation of HK (and Factor XII) binding sites along endothelial cell membranes consists of bimolecular complexes of gC1qR-cytokeratin 1 and u-PAR-cytokeratin 1, with gC1qR binding being favored.
Keywords: Endothelial cells; high molecular weight kininogen; gC1qR; cytokeratin 1; u-PAR